MO006INFLAMMASOME ACTIVATOR NLRP3 HYPOMETHYLATION IS ASSOCIATED WITH GLUCOCORTICOID RESISTANCE IN PATIENTS WITH IDIOPATHIC NEPHROTIC SYNDROME. (6th June 2020) - Granata, Simona; Stocco, Gabriele; Lucafò, Marianna; Bonten, Erik; McCorkle, Robert; Decorti, Giuliana; Gambaro, Giovanni; Evans, William E; Zaza, Gianluigi
Abstract: Background and Aims: We have previously shown that the Nod-like receptor protein-3 (NLRP3) gene is over-expressed in leukocytes of many patients with chronic kidney disease, and studies have also shown that hypomethylation and overexpression of NLRP3 are associated with glucocorticoid resistance in acute lymphoblastic leukemia. Therefore, we hypothesized that hypomethylation of the NLRP3 promoter my cause glucocorticoid resistance in patients with Idiopathic Nephrotic Syndrome (INS) associated with minimal change disease (MCD) or focal glomerulosclerosis (FSGS). Method: We assessed NLRP3 and Caspase 1 (CASP1) promoter methylation by SNuPE reaction in germline DNA from leukocytes of 14 glucocorticoid-resistant and 18 glucocorticoid-sensitive adult INS patients (discovery cohort) and 7 glucocorticoid-resistant and 14 glucocorticoid-sensitive pediatric INS patients with MCD/FSGS (validation cohort). The effects of NLRP3 inflammasome on glucocorticoid resistance were validated in vitro in human monocytic cell lines (THP-1 and U937). Results: Methylation of CpG islands in the CASP1 promoter was undetectable in both groups whereas NLRP3 promoter methylation was significantly lower in glucocorticoid-resistant compared to glucocorticoid-sensitive in both adults and children. The AUROC curve was 81.2% (p=0.0003) in adults and 73.5% (p=0.0002) in children demonstrating the capability of NLRP3 methylation to discriminate glucocorticoid-resistant versus glucocorticoid-sensitive. Activation of the NLRP3 inflammasome by LPS/ATP reduced glucocorticoid receptor expression and increased glucocorticoid resistance in U937. Consistently, knockdown of NLRP3 in THP-1 increased sensitivity to glucocorticoids. Conclusion: Our findings demonstrate a novel mechanism whereby INS patients develop resistance to glucocorticoids via leukocyte epigenetic changes of NLRP3 and reveal a new potential clinical biomarker to early detect this condition.